Land Suitability of Tunjung Plateau of Barongtongkok Regency for Rain-Fed Upland and Bunded Rice Cultivation, East Kalimantan - Mulyadi, Mulyadi; Makhrawie, Makhrawie; Dhonanto, Donny (Mulawarman University, 2025)
Land conversion is a seriousthreat to efforts to increase rice production in Indonesia. Effort are needed to improve the welfare of farmers so that the land does not change function so that the land continous to produce rice suitanability. This study aimed to obtain information about the land characteristics for rain-fed upland and bunded rice on old vulcanic parent materials in Barongtongkok of East Kalimantan. The soil profile have been done by team of JICA, and selected at two different physiographic i.e. on almost flate and undulating topography. The climate used from available data as close as possible by location study, where both climate data (rainfall, temperature, and relative humidity) and soil profile, chemical analyzed data used to evaluate according to FAO soil evaluation system modified by Sys and Van Ranst (1993) and classified the soil using Key to soil taxonomy (USDA, 2022). In general, the climate characteristics of Barongtongkok climate are suitable (S2) for upland and bunded rice cultivation due to relative humidity and sun-shine hours on growing season. Base on the pedon analyzed, the soil of Bangun Sari village classified as actually moderately suitable (S3ctf) but potentially suitable (S2ct) and actually unsuitable (N1ctf) for upland rice, unsuitable (N1ctf) but potentially suitable (S3ct) for bunded rice. Moderately suitable (S3cf) and unsuitable (N1cf) for upland and bunded rice but potentially suitable (S2c) in Ma. Asa, Johan Asa and Galeo Asa villages. Land evaluation of Asa, Galeo Baru and Engkuni villages, actually unsuitable (N1cf) but potentially suitable (S2c) of both of land utilization type. Soil of the study area has highly developed and show low activity clay (CEC clay less than 16 C mol (+) and Isohyperthermic temperature and perudic soil moisture regime, clasified as Andic Kandiperox (Asa and Galeo Baru villages), Typic Kandiperox (Engkuni village). The soil less developed in Bangun Sari village (Eutric Humudepts), and more developed in Ma. Asa, Galeo Asa dan Jihan Asa (Andic Palehumults).